Honouring the Maradika: from Kaili kingdoms to a decentralised neo-royal provincial government - Santaella, Mayco Axel * (BRILL, 2024)
Music, dance and ceremonies associated with Kaili royalty depict the presence of ethnic-specific genres and the exchange of tangible and intangible heirlooms (pusaka) with neighbouring kingdoms. Located in Central Sulawesi, Kaili lands (ngata Kaili) experienced the formation of distinct kingdoms at the periphery of four historical centres, namely South Sulawesi, East Kalimantan, the Sulu Zone and Maluku. With shared practices as an ethnicity (Kaili) and idiosyncrasies with distinct courts, dialects and lineages, Kaili kingdoms maintained a legacy of traditions serving as status signifiers in honour of nobility circles (maradika), and a heritage signifying local customs of each court and links to other kingdoms. The Kaili heritage experienced changes together with the transformations of the Indonesian political climate after independence in 1945, particularly during the national process of centralisation and standardisation of the performing arts during the New Order (Orde Baru) era (1967– 1998), and once again during the process of decentralisation of government operations that gave a greater autonomy to the performing arts after 1998. In view of the dynamic, evolving and adapting role of Kaili performance traditions associated with the nobility, this chapter analyses the forms in three diachronic eras: the Kaili kingdoms before 1945; the centralised national Indonesian government after 1945; and the decentralised neo-royal provincial government in Central Sulawesi after 1998. The chapter considers the following as examples of performing arts development for each era: the Kaili vaino mourning song in remembrance of deceased royalty and the balia healing ritual forms performed for royalty; royal links of the kakula gong-row heritage; and the pajoge maradika royal dance form.